2015
DOI: 10.1364/oe.23.033350
|View full text |Cite
|
Sign up to set email alerts
|

Angle- and position-insensitive electrically tunable absorption in graphene by epsilon-near-zero effect

Abstract: We propose an electrically tunable absorber based on epsilon-near-zero (ENZ) effect of graphene embedded in a nanocavity, which is composed of metal grating and substrate. Due to strong surface-normal electric field confined in ENZ graphene in the proposed structure, greatly enhanced light absorption (~80%) is achieved in an ultrathin graphene monolayer. By electrically controlling the Fermi-level of graphene, a sharp peak absorption wavelength is tuned over a wide range. The proposed device can work as an opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…When a single sheet of graphene is placed on top of the silver grooves, there will be a dominant component electric field (E y ) parallel to the graphene sheet that matches the direction of the graphene plane. It should be additionally noted that in some literature the graphene was theoretically defined as an isotropic material, in which an epsilon-near-zero effect was observed that accounts for a very strong modulation capability [20][21][22]. However, further analyses [23] and experimental results [18] did not confirm this property, and an anisotropic graphene model with in-plane conductivity we used here should be the correct one.…”
mentioning
confidence: 73%
“…When a single sheet of graphene is placed on top of the silver grooves, there will be a dominant component electric field (E y ) parallel to the graphene sheet that matches the direction of the graphene plane. It should be additionally noted that in some literature the graphene was theoretically defined as an isotropic material, in which an epsilon-near-zero effect was observed that accounts for a very strong modulation capability [20][21][22]. However, further analyses [23] and experimental results [18] did not confirm this property, and an anisotropic graphene model with in-plane conductivity we used here should be the correct one.…”
mentioning
confidence: 73%
“…Note that remaining parameters are fixed unless otherwise stated; that is, n H  = 3.0, n L  = 1.5, Period  = 0.9 μm, FF  = 0.43, and the graphene thickness is 0.34 nm.) The complex permittivity of graphene ( ε g ) was extracted from the Kubo formula for the Fermi-level of E f  = 0 eV (undoped) and a mobility of Mo  = 0.5 m 2 /Vs 21, 22 , unless otherwise stated. The spectra showed two transmission dips within the frequency range of our interest when n Slab  < ~2.7 or n Slab  > ~3.4.…”
Section: Resultsmentioning
confidence: 99%
“…6(a), where tuning the peak absorption wavelength over ~300 nm is achieved by simply adjusting n Slab from 2.28 to 3.25 while keeping A > 95%. For the tunable operation of the “ triple - mode absorber ”, electro-optic materials such as liquid crystals 22, 23 can be used for the slab, and additional electrodes to apply a voltage will be required. In contrast, the “ dual - mode absorber “ designed above shows a much narrower tuning range of ~20 nm via the variation of n H from 2.980 to 3.022 for the same level of maximum absorption (A > 95%) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned in Section 1, several researchers have studied the properties of graphene in recent years [22,23,30]. This material has attracted much attention because of its exceptional properties, such as tunable bandgap [31,32], extremely high in-plane stiffness (Young's modulus), superior (highest ever measured) strength [33], high tensile strength [34], ultra-lightweight, thin nature owing to its 2D nature [17], tunable absorption, and many other factors [35,36]. In this work, we focus on graphene absorption in order to employ its properties in the proposed microdevice.…”
Section: Optical Design and Analysismentioning
confidence: 99%